Sociodemographic and Provider Based Disparities in the Management of Stage I Testicular Cancer. Issue 1 (January 2017) - Agarwal, Gautum; Sharma, Pranav; Valderrama, Oscar; Lin, Hui‐Yi; Yue, Binglin; Nguyen, Sabine; Fishman, Mayer; Luchey, Adam; Pow‐Sang, Julio M.; Spiess, Philippe E.; Poch, Michael A.; Sexton, Wade J.
Abstract : Introduction: : The treatment paradigm for stage I testicular cancer has changed in the setting of accurate staging, reliable followup and a greater understanding of treatment related side effects. We assessed the influences on management decisions in patients with stage I testicular cancer. Methods: : We retrospectively identified 121 patients with stage I testicular cancer who were evaluated at our institution from 1999 to 2013. Sociodemographic characteristics, pathological features and provider specific factors were compared in patients who underwent surveillance vs treatment. Differences in medians and proportions were determined using the Kruskal‐Wallis and chi‐square tests. Multivariate logistic regression analysis was performed to identify independent predictors of treatment. Results: : A total of 87 patients had stage I nonseminomatous germ cell tumor and 34 had pure seminoma. Patients with nonseminomatous germ cell tumor who were evaluated before 2011 and those seen by urological oncologists were more likely to undergo primary retroperitoneal lymph node dissection (p <0.01). Patients with nonseminomatous germ cell tumor who were evaluated by medical oncologists more often received chemotherapy (p <0.01). For nonseminomatous germ cell tumors treatment was independently associated with advanced tumor stage and lymph node invasion (OR 15.3, 95% CI 3.26–71.95, p = 0.001). In patients with pure seminoma the use of radiation therapy decreased from 40% to 5% after 2010 while surveillance increased from 47% to 74% (p = 0.056) and no recorded variable was predictive of treatment. Conclusions: : Advanced stage and lymph node invasion in patients with stage I nonseminomatous germ cell tumor are drivers of treatment. Management also depends on the specialty of the treating provider, suggesting the possibility of bias during patient counseling. In turn, this suggests the need for patient assessment through a multidisciplinary approach.